2017
DOI: 10.1038/ncomms15516
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Zak phases and topological invariants in a chiral quantum walk of twisted photons

Abstract: Topological insulators are fascinating states of matter exhibiting protected edge states and robust quantized features in their bulk. Here we propose and validate experimentally a method to detect topological properties in the bulk of one-dimensional chiral systems. We first introduce the mean chiral displacement, an observable that rapidly approaches a value proportional to the Zak phase during the free evolution of the system. Then we measure the Zak phase in a photonic quantum walk of twisted photons, by ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
336
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 320 publications
(347 citation statements)
references
References 57 publications
9
336
1
1
Order By: Relevance
“…These states are not protected by the chiral symmetry, and therefore not robust against (chiral-preserving) disorder. In order to illustrate this fact, we add a spatial disorder in the operator W: the hoppings of the Hamiltonian of W are multiplied by a factor 1  + ( ), where ò is a random number in the rangeThe right side of the energy spectrum (after the dashed line) in figure 6(b) shows clearly that, whereas the 0 and the p-energy states remain unaffected, the unprotected states change of energy when disorder is applied.The effect of spatial disorder and noise on the mean chiral displacement for systems with 2  = were already discussed at length in our previous publication, [24]. In particular, there we confirmed that this observable is a robust topological marker by showing that, in presence of chiral-preserving static spatial disorder of amplitude small compared to the gap, the ensemble average of the mean chiral displacement smoothly converges to the value obtained for a clean system.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…These states are not protected by the chiral symmetry, and therefore not robust against (chiral-preserving) disorder. In order to illustrate this fact, we add a spatial disorder in the operator W: the hoppings of the Hamiltonian of W are multiplied by a factor 1  + ( ), where ò is a random number in the rangeThe right side of the energy spectrum (after the dashed line) in figure 6(b) shows clearly that, whereas the 0 and the p-energy states remain unaffected, the unprotected states change of energy when disorder is applied.The effect of spatial disorder and noise on the mean chiral displacement for systems with 2  = were already discussed at length in our previous publication, [24]. In particular, there we confirmed that this observable is a robust topological marker by showing that, in presence of chiral-preserving static spatial disorder of amplitude small compared to the gap, the ensemble average of the mean chiral displacement smoothly converges to the value obtained for a clean system.…”
supporting
confidence: 70%
“…The second one is to measure the response to an external change. The observation of edge states [11,21,30,31] and the measurement of the winding number through the mean chiral displacement [24] belong to the first category. The measurement of the winding number by interferometric architectures [6,25], by introducing losses [15,32,33], and by scattering measurements [22] belong to the second category.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations